Employability Management Needs Analysis for the ICT sector in Europe: The Case of Small and Medium-sized Enterprises - van der Heijden, Beatrice I. J. M. (2010)
The purpose of this paper is to deal with the outcomes of a so-called “employability management needs analysis” that is meant to provide more insight into current employability management activities and its possible benefits for Information and Communication Technology (ICT) professionals working in Small- and Medium-sized enterprises (SMEs) throughout Europe. A considerable series of interviews (N=107) were conducted with managers in SMEs in seven European countries, including Germany, Greece, Italy, the Netherlands, Norway, Poland, and the UK. A semi-structured interview protocol was used during the interviews to cover three issues: employability (13 items), ageing (8 items), and future developments and requirements (13 items). Analysis of all final interview transcriptions was at a national level using an elaborate common coding scheme.